Electroporation-derived melanoma extracellular particles activate fibroblasts - Choromańska, Anna; Szwedowicz, Urszula; Szewczyk, Anna; Daczewska, Małgorzata; Saczko, Jolanta; Kruszakin, Roksana; Pawlik, Krzysztof J.; Baczyńska, Dagmara; Kulbacka, Julita (Biochimica et biophysica acta. General subjects, 2024)
Although the pulse electric field (PEF) has been used in electrochemotherapy (ECT) for many years, the kinetics and profile of extracellular particles (EPs) released as a result of reversible electroporation have yet to be studied. It also needs to be clarified whether and how the profile of released EPs depends on the parameters of the applied PEF. The presented studies investigated the effect of EPs released from human melanoma cells after various parameters of reversible electroporation on markers indicating EP-mediated transformation of normal fibroblasts into tumor-associated fibroblasts. The expression levels of the vascular cell adhesion molecule-1 (VCAM-1) and changes in the expression of phosphor-histone H3 (pHH3), a biomarker specific for cells in mitosis, cell viability, and the migration capacity of the studied fibroblast cells, were analyzed. EPs were isolated from two commercial malignant melanoma cell lines previously subjected to reversible electroporation. Human primary fibroblasts (HPFs) were selected for EPs exposure. It was observed that after incubation with melanoma-derived EPs, HPFs showed differences in cell viability, migration capacity, VCAM-1, pHH3, and N-cadherin expression, depending on PEF parameters and the grade of melanoma cells. This study highlights that small extracellular particles (sEPs) from cancer cells can promote metastasis by carrying specific signals that lead to the upregulation of molecules like FAK, MMP-9, and N-cadherin in recipient cells. [Display omitted] •Melanoma-derived EPs alter fibroblast viability and migration, varying with PEF parameters and EP size.•Melanoma-derived EVs alter fibroblast transformation markers, varying with PEF parameters and EP size.•Small EPs from melanoma cells facilitate metastasis by upregulating FAK, MMP-9, and N-cadherin in recipient cells.